ขององค์การบริหารส่วนตำบลท่าธง อำเภอรามัน จังหวัดยะลา Guidelines for Flood Preparedness and Response of Tatong Sub-District Administrative Organization, Raman District, Yala Province - บือราเฮง, ฟาตีฮะห์; วาแมดีซา, อัฟนาน; บินอิสริส, วันฮารงค์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to (1) study the problems and obstacles in the implementation of preparedness and response to flood disasters and (2) study the approaches to preparedness and response to flood disasters of the Subdistrict Administrative Organization. This research is a qualitative study that collected data through in-depth interviews and document study from 22 key informants. The data were analyzed using content analysis. The research results found that the preparedness and response to flood disasters of the Subdistrict Administrative Organization still encounter several problems and obstacles, including: (1) communication and warning systems that are not yet thoroughly accessible, (2) disaster prevention and mitigation plans lacking regular drills, (3) limitations in equipment and budget, and (4) the participation of the public that is not continuous. These issues affect management during disaster situations, resulting in a lack of flexibility in some aspects. For development guidelines, there should be the preparation and improvement of preparedness plans to make them clear and practically applicable. In addition, regular drills for flood disaster response plans should be organized, warning systems should be developed to be faster and accessible to all groups of people, and public participation should be promoted. Furthermore, cooperation networks should be established among government agencies, community leaders, and volunteers, along with continuous budget support, in order to make flood disaster management more effective, reduce losses, and create sustainable safety for people in the area